Dilemmas regarding the management of endometriosis-related infertility - Simopoulou, Mara; Sfakianoudis, Konstantinos; Tsioulou, Petroula; Rapani, Anna; Pantos, Konstantinos; Koutsilieris, Michael (Annals of Research Hospitals, 2019)
Endometriosis depicts a chronic disease characterized by the invasion of endometrial—like tissues outside the uterine cavity, inducing female infertility. The idiopathic nature of endometriosis, the ambiguous invasive diagnosis—mainly through laparoscopy—and the lack of a definitive optimal treatment challenge both clinicians and researchers. This perspective article intends to present the current controversies in the context of the clinical management of endometriosis-related infertility. The establishment of a widely accepted standardized protocol, in line with the decryption of the molecular mechanisms underlying the disease, may represent the holy grail of endometriosis-related infertility investigation.